TNI Guarding the Prosecutor's Office Considered in Harmony with Prabowo's Asta Cita (International Forum of Researchers and Lecturers, 2025)
The deployment of TNI soldiers has caused controversy because it is considered to strengthen militarism in civilian institutions. The Attorney General's Office, TNI, and the Chief of Police have spoken out regarding the deployment of TNI soldiers to guard the Attorney General's Office Complex, as well as all High Prosecutors' Offices and District Prosecutors' Offices throughout Indonesia. This policy has attracted criticism from academics, observers, and civil society organizations, who argue that the involvement of the military in civilian institutions risks undermining democratic principles and civilian supremacy. The debate reflects Indonesia’s historical context, where the military once played a dual role in both defense and civilian governance, raising concerns that such practices may resurface. The deployment of TNI soldiers in the Prosecutor’s Office security system is an order from the TNI Commander as a form of cooperation with the Attorney General's Office. The order is explicitly stated in the TNI Commander’s Telegram Number TR/442/2025 dated May 6, 2025. Furthermore, this cooperation is formalized through a Memorandum of Understanding (MoU) between the TNI and the Indonesian Prosecutor’s Office, namely Memorandum Number NK/6/IV/2023/TNI dated April 6, 2023. The MoU outlines eight areas of collaboration, including: (1) education and training; (2) exchange of information for law enforcement purposes; (3) assignment of TNI soldiers within the Prosecutor’s Office environment; and (4) assignment of prosecutors as supervisors at the TNI General Auditorate. These points are intended to strengthen coordination, improve institutional capacity, and foster synergy in law enforcement and security.